Fluorescein isothiocyanate labeled, magnetic nanoparticles conjugated D-penicillamine-anti-metadherin and in vitro evaluation on breast cancer cells - Akça, Özlet; Ünak, Perihan; Medine, E.İlker and Özdemir, Çağlar and Sakarya, Serhan and Timur, Suna (Revista Brasileira de Física Médica, 2015)
Silane modified magnetic nanoparticles were prepared after capped with silica generated from the hydrolyzation of tetraethyl orthosilicate (TEOS). Amino silane (SG-Si900) was added to this solution for surface modification of silica coated magnetic particles. Finally, D-penicillamine (D-PA)-antimetadherin (anti-MTDH) was covalently linked to the amine group using glutaraldehyde as cross-linker. Magnetic nanoparticles were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), and atomic force microscopy (AFM). AFM results showed that particles are nearly monodisperse, and the average size of particles was 40 to 50 nm. An amino acid derivative D-PA was conjugated anti-MTDH, which results the increase of uptaking potential of a conjugated agent, labelled fluorescein isothiocyanate (FITC) and then conjugated to the magnetic nanoparticles. In vitro evaluation of the conjugated D-PA-anti-MTDH-FITC to magnetic nanoparticle was studied on MCF-7 breast cancer cell lines. Fluorescence microscopy images of cells after incubation of the sample were obtained to monitor the interaction of the sample with the cancerous cells. Incorporation on cells of FITC labeled and magnetic nanoparticles conjugated D-PA-anti-MTDH was found higher than FITC labeled D-PA-anti-MTDH. The results show that magnetic properties and application of magnetic field increased incorporation rates. The obtained D-PA-anti-MTDH-magnetic nanoparticles-FITC complex has been used for in vitro imaging of breast cancer cells. FITC labeled and magnetic nanoparticles conjugated D-PA-anti-MTDH may be useful as a new class of scintigraphic agents. Results of this study are sufficiently encouraging to bring about further evaluation of this and related compounds for ultraviolet magnetic resonance (UV-MR) dual imaging.